E-Commerce Pandemic Covid-19 Home Industries and SMEs - D Kurniasih; F M Akbar (International Journal of Research and Applied Technology (INJURATECH), 2021)
This study aims to identify and analyze the impact of the Covid-19 on the home industry and SMEs sector. The research method used was a literature study. Literature study is method research conducted by examining ten previous studies on strategies to survive the SMEs during the pandemic. Small and medium enterprises (SMEs) are on the edge of a cliff. The Covid-19 pandemic caused the economic downturn. The lockdown stopped economic activity, reduced demand, and reduced interactions with others. At the beginning of the lockdown, SMEs one by one suffered losses and went bankrupt. The impact of the Covid-19 pandemic on the home industry and SMEs sector is certainly influential because it has made a significant contribution to the economy in this field. The results showed that the use of information technology had been applied quite widely in various areas. Quite a lot of offline shops have also tried to open shops online, e-commerce sites, and even web e-commerce, apart from being accessed via the web, are also widely available. From the use of computers and the internet in managing their business. The conclusion that millennial customers' online buying interest during the Covid-19 outbreak was not influenced by product prices but influenced by millennial customer trust.